Relationship attribution causal skill to perform the background rolling annexation on the table in artistic gymnastics at the students in the faculty of physical education and sports science in Baghdad. - Hassan, Taraq; Rasul, Janan (Journal of Physical Education, 2015)
Identify the causal attribution to the student of physical education college in artistic gymnastics , understand the performance of the basic background rolling annexation on the table ground movements , understand the correlation between the dimension of causal attribution and perform of the basic background rolling annexation on the table ground movements, the hypothesis of search , there is a statistically correlation between the dimension of causal attribution and perform of the basic background rolling annexation on the table ground, use descriptive approach , the sample included students of the second phase , skills have been identified and evaluated , after data collection , analysis and processing statically was reached some of the most important conclusion between the performance of the skill of the background rolling annexation on the table ground and movements attributed the good and poor performance